Iodine-mediated ring closing alkene iodoamination with N-debenzylation for the asymmetric synthesis of polyhydroxylated pyrrolidines - Davies, S; Nicholson, R; Price, P; Roberts, P; Smith, A (2004)
An iodine-mediated ring closing alkene iodoamination with N-debenzylation protocol provides a direct route for the asymmetric synthesis of polyhydroxylated pyrrolidines from homochiral β-amino acid derivatives.